The Structuring Teaching Core (NDE): The Experience of a Brazilian Institution of Higher Education - Mayara Rohrbacher Sakr; Alboni Marisa Dudeque Pianovski Vieira (Revista Iberoamericana de Evaluación Educativa, 2019)
The article analyzes the regulation, the dynamics of operation and the contribution of the Structuring Teaching Core (NDE) for the development of higher education courses. Its objective is to analyze the perception and performance of NDE teachers from a Brazilian public university, private, non-profit. This is a case study with a qualitative approach, based on exploratory and descriptive research modalities, using individual and face-to-face interviews. The interviewed teachers reported aspects such as operational characteristics; cultural paradigm issues; visualization of the need, limits and potentialities of the nucleus and concluded that their functions go beyond administrative functions, having a highly pedagogical character.